Developing an Achievement Test in Light of the Specifications Table (Journal Of Educational and Psychological Researches, 2023)
AbstractThe research addresses the specification table and the extent of its use in developing achievement tests, as well as detects the obstacles to its use through a sample of (120) respondents from the faculty members in some Baghdad schools and colleges. After unpacking and processing the data statistically, the research reached several results: the study sample do not use the test map in the development of their tests, as their percentage reached (82%) and there are no statistically significant differences in the use of the specification table by the sample members according to their place of work or the number of years of experience. The results also revealed the most important reasons that prevent the use of the specification table in developing the achievement test, which are the lack of knowledge of the teachers about it, the lack of benefit of its application, mainly because their experience is sufficient to build a good test. Afterward, the researcher presented an analytical study of the specification table upon several axes and suggested some simplified forms to employ in the planning of achievement tests.